2013
DOI: 10.1016/j.tiv.2013.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nicotine, its metabolites and tobacco extracts on human platelet function in vitro

Abstract: The present study investigated in vitro effects of nicotine, its major metabolites, tobacco extracts and extract of tobacco-free snuff on human platelets. None of the metabolites cotinine, cotinine-N-oxide, nicotine-1´-N-oxide or trans-3´-hydroxycotinine (0.1-10 µM) affected platelet aggregation or P-selectin expression. Nicotine (10 µM) weakly increased platelet aggregation, whereas trans-3´-hydroxycotinine (0.1 µM) and nicotine-1´-N-oxide (1-10 µM) weakly inhibited adhesion to fibrinogen. To elucidate the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 48 publications
(54 reference statements)
1
13
1
1
Order By: Relevance
“…While cigarette smoke in general leads to increased platelet activation [13][14][15][16][17][18], nicotine itself was reported to have protective effects in platelet function [23][24][25][26]. This inconsistency is probably attributed to the exceptional characteristics of nicotine itself [33] and the inability to separate the effect of nicotine from those of additional tobacco ingredients [34]. In our study, we could not confirm the reported differences in platelet degranulation, fibrinogen receptor activation and platelet aggregation between the smokers and nonsmokers.…”
Section: Discussioncontrasting
confidence: 77%
“…While cigarette smoke in general leads to increased platelet activation [13][14][15][16][17][18], nicotine itself was reported to have protective effects in platelet function [23][24][25][26]. This inconsistency is probably attributed to the exceptional characteristics of nicotine itself [33] and the inability to separate the effect of nicotine from those of additional tobacco ingredients [34]. In our study, we could not confirm the reported differences in platelet degranulation, fibrinogen receptor activation and platelet aggregation between the smokers and nonsmokers.…”
Section: Discussioncontrasting
confidence: 77%
“…Ljungberg et al performed nicotine infusion studies to assess nicotine metabolism on platelet activity. 75 Their findings support in vitro studies performed by our group (unpublished data), demonstrating that nicotine and some metabolites do not overtly activate platelets. However, they found that nicotine exposure marginally inhibited platelet attachment to extracellular matrix (ECM) components, such as collagen.…”
Section: Platelets Nicotine and Tobaccosupporting
confidence: 82%
“…It is noteworthy that exposure to some of these toxicants, albeit from traditional tobacco smoking and other sources, was found to be associated with an enhanced platelet activation phenotype 6. Furthermore, while the effects of nicotine on platelet activation/aggregation are still controversial,16, 105, 106, 107, 108 particulate matter109, 110 and acrolein93 were indeed found to enhance platelet function.…”
Section: Discussionmentioning
confidence: 99%